Climate-induced migrant's hopeful journey toward security: Pushing the boundaries of gendered vulnerability and adaptability in Bangladesh - Khanom, Sufia; Tanjeela, Mumita; Rutherford, Shannon (Frontiers in Climate, 2022)
Every year 10,000 climate-induced migrants in Bangladesh leave their homes seeking safer locations away from the climate-induced disasters they have experienced. They commonly migrate to nearby urban areas or the capital city after losing their livelihoods in their place of origin. However, the unplanned urbanization, limited capacities of urban infrastructures, service sector deficiencies, man-made disasters and other social vulnerabilities further push these migrants into an (in)secure state. Hopes of security and capacity to adapt in their new homes, can be impacted by the patriarchal society where gender is often associated with unequal social relations and hierarchies. These might extend from every day to long term (in)security. This paper draws on qualitative data collected as part of research conducted for two PhD projects. In both cases, climate-induced migrants were forced to migrate from their places of origin due to sea level rise, river erosion or soil salinity to Dhaka (capital city) or Coxes Bazar (coastal city) in Bangladesh. In this context, we seek to answer: are their adaptive capacities influenced by gender relations? How are these adaptive capacities shaped through different institutions? And, how can these adaptive actions improve/strengthen human security? Gendered power relations are the main analytical framework for this paper as power is an influential factor to shape adaptive capabilities. We argue that (in)security, as an outcome of unsustainable adaptability, further push climate-induced migrants in vulnerable conditions in their newly settled urban areas. The vulnerability, capacity to adapt and (in)security are gendered. These findings help to better understand for whom, where and how the exclusive adaptative initiatives can further place climate-induced migrants in vulnerable and (in)secure conditions in their newly settled areas and hence identify resource and policy needs as this climate-induced migration continues arising from the projected changes arising from the warming planet.